2014
DOI: 10.1620/tjem.234.189
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Transcranial Direct Current Stimulation on Central Post-Stroke Pain

Abstract: Pain that occurs after a stroke lowers the quality of life. Such post-stroke pain is caused in part by the brain lesion itself, called central post-stroke pain. We investigated the analgesic effects of transcranial direct current stimulation (tDCS) in stroke patients through quantitative sensory testing. Fourteen participants with central post-stroke pain (7 female and 7 male subjects) were recruited and were allocated to either tDCS (n = 7) or sham-tDCS (n = 7) group. Their ages ranged from 45 to 55 years. tD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 35 publications
1
74
0
2
Order By: Relevance
“…Stimulation of primary motor cortex (M1) appears to be the most effective cortical target (Nguyen et al, 1999; Kumar and Soni, 2009; Hirabayashi et al, 2011; DosSantos et al, 2012; Fregni et al, 2014; Brietzke et al, 2015; Cioato et al, 2015; Morishita et al, 2015; Oh and Seo, 2015). Analgesia is believed to be achieved through the stimulation of M1-thalmic relays to reduce hyperactivity in thalamic linked pain networks (Tsubokawa et al, 1993; Mertens et al, 1999; Khedr et al, 2005; Garcia-Larrea and Peyron, 2007; Peyron et al, 2007; Lima and Fregni, 2008; Nguyen et al, 2008; Fontaine et al, 2009; Lefaucheur et al, 2009; Ohn et al, 2012; Bae et al, 2014; Hasan et al, 2014; Lefaucheur, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of primary motor cortex (M1) appears to be the most effective cortical target (Nguyen et al, 1999; Kumar and Soni, 2009; Hirabayashi et al, 2011; DosSantos et al, 2012; Fregni et al, 2014; Brietzke et al, 2015; Cioato et al, 2015; Morishita et al, 2015; Oh and Seo, 2015). Analgesia is believed to be achieved through the stimulation of M1-thalmic relays to reduce hyperactivity in thalamic linked pain networks (Tsubokawa et al, 1993; Mertens et al, 1999; Khedr et al, 2005; Garcia-Larrea and Peyron, 2007; Peyron et al, 2007; Lima and Fregni, 2008; Nguyen et al, 2008; Fontaine et al, 2009; Lefaucheur et al, 2009; Ohn et al, 2012; Bae et al, 2014; Hasan et al, 2014; Lefaucheur, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…While EBS, TMS, and tDCS have shown some clinical success in treating CPSP, high variability across studies has impeded their widespread acceptance (Mertens et al, 1999; Lefaucheur et al, 2004, 2009; Lima and Fregni, 2008; Nguyen et al, 2008; Fontaine et al, 2009; DosSantos et al, 2012; Bae et al, 2014; Lefaucheur, 2016). Upward of 30% of EBS patients do not respond to stimulation (Tsubokawa et al, 1993; Katayama et al, 1998; Mertens et al, 1999; Nguyen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors clearly showed the analgesic effect of tDCS in fibromyalgia, 23 spinal cord injury, 18,21 and post-stroke pain 53,57 using RCTs. It is possible that tDCS has greater effect for unprovoked types of pain, as observed by Cecilio et al, 13 than for provoked pain conditions like PVD.…”
Section: Commentmentioning
confidence: 98%
“…Transcranial direct current stimulation (tDCS) is a non‐invasive method of cerebral stimulation that may represent a promising tool for modulating trigeminal nociceptive processes and decreasing the pain response (Hagenacker et al, ). It has been used in the treatment of several pain conditions in patients, such as central poststroke pain (Bae, Kim, & Kim, ); it has also been tested in animal pain models, including mechanical allodynia in chronically stressed rats (Spezia Adachi et al, ) and neuropathic (Cioato et al, ) or inflammatory pain (Laste et al, ).…”
Section: Introductionmentioning
confidence: 99%